2022
DOI: 10.3390/vetsci9020062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Phylogenetic Analysis of Spirometra Tapeworms from Snakes in Hunan Province

Abstract: Sparganosis is a neglected zoonotic parasitic disease that poses huge threats to humans worldwide. Snakes play an important role in sparganosis transmission because they are the most common second intermediate hosts for Spirometra parasites. However, the population genetics of Spirometra isolates from snakes is currently not well studied in China. The present study was performed to explore the molecular characteristics and phylogenetic analysis of Spirometra tapeworms from different species of snakes in Hunan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The translated sequences were blasted against PoIFN sequences in GenBank for homology, conserved cysteine residues and potential N-glycosylation sites using the BLAST algorithm (https://blast.ncbi.nlm.nih.gov/Blast.cgi, accessed on 2 December 2022). The amino acid sequences were further aligned with that of 11 different animal species (Supplemental Table S1) for sequence homologies (Clustal W scores) using the MegAlign program [22].…”
Section: Gene Cloning and Sequence Analysismentioning
confidence: 99%
“…The translated sequences were blasted against PoIFN sequences in GenBank for homology, conserved cysteine residues and potential N-glycosylation sites using the BLAST algorithm (https://blast.ncbi.nlm.nih.gov/Blast.cgi, accessed on 2 December 2022). The amino acid sequences were further aligned with that of 11 different animal species (Supplemental Table S1) for sequence homologies (Clustal W scores) using the MegAlign program [22].…”
Section: Gene Cloning and Sequence Analysismentioning
confidence: 99%
“…ACF, whose matrix is a molecular structure specially designed viscoelastic polyurethane, is a novel mixed cellular material and a biomimetic metamaterial with a three-dimensional ultrastructure similar to human cartilaginous tissue ( Wang B. et al, 2020 ). Electron and atomic force microscopic scanning showed that the surface of ACF is distributed with connective micron-sized pores with a shape close to circular and nanoscale bumps ( Chen S. et al, 2022 ). It can absorb up to 97.1% of the impact energy, and the energy-absorbing capacity only decreases by 0.4% after five impacts ( Chen S. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Electron and atomic force microscopic scanning showed that the surface of ACF is distributed with connective micron-sized pores with a shape close to circular and nanoscale bumps ( Chen S. et al, 2022 ). It can absorb up to 97.1% of the impact energy, and the energy-absorbing capacity only decreases by 0.4% after five impacts ( Chen S. et al, 2022 ). Its cushioning and energy absorption performance significantly exceeds those of ordinary cushioning materials ( Wang B. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%